Changes in plant cover and functional traits induced by grazing in the arid Patagonian Monte - Bar Lamas, Marlene Ivonne (2013)
Grazing disturbance may affect the structure and functioning of arid rangelands. We analyzed the changes in plant cover and plant functional traits (plant height, SLA, N in green leaves) at the community, morphotype and species level in relation to grazing disturbance in arid ecosystems with more than 100 years of sheep grazing history. We identified two grazing areas and within each area we selected two representative and homogeneous sites located far (low grazing disturbance) and near (high grazing disturbance) from the single permanent watering point. We evaluated the plant cover at community, morphotype (evergreen tall shrubs, deciduous shrubs, dwarf shrubs, perennial herbs and perennial grasses) and species level at each site and randomly selected three individuals of modal size of each species to evaluate at them the selected plants traits. Plant cover was reduced by grazing disturbance at the community level. The cover of perennial grasses and evergreen tall shrubs decreased and that of dwarf shrubs increased with increasing grazing disturbance. Increasing cover of dwarf shrubs did not compensate the cover reduction of the other morphotypes. In contrast, plant height, SLA and N in green leaves were not affected by high grazing disturbance at community level as a consequence of positive and negative changes in these traits at morphotype and species levels induced by high grazing disturbance. We concluded that cover was the trait most affected by high grazing disturbance and positive and negative changes in other traits at plant morphotype or species level did not affect community attributes related to resistance against herbivory.